(untitled) (Baghdad Science Journal, 2025)
Despite the fact that women face the lower risk of cardiovascular morbidity and mortality than men before menopause, they have the same or higher risk if they develop diabetes. To compare the sex differences in cardiovascular disease (CVD) risk factors among adult diabetic and non diabetic patients Case control study. The specialized center for Endocrinology and Diabetes (SCED) and outpatient Medical-Clinic at Al–Kindy Teaching Hospital, for the period from January to December-2008. 314 diabetic patients (152 males & 162 females) and 136 of non diabetic patients (72 males &64 female) as control group. All the selected participants were adults (18 – 35) years old. All participants were assessed for CVD risk factors, including family history, smoking status, physical activity, Body mass index, central obesity, hypertension, hypercholestremea, hyperlipidemea and uncontrolled hyperglycemia. The gender difference between men and women, in both diabetic and non diabetic patient, had been studied. Sex difference in CVD risk factors (hypertension, hypercholestremia, hyperlipidemea, smoking and leisure physical activity) had been found to be statistically significant among non diabetic subjects. This significant difference was diminished in diabetic patients for all the risk factors but not for smoking habits and leisure physical activity habits. The burden of conventional CVD risk factors in the presence of diabetes was greater in women than in men at baseline. Prospectively, hypertension, hypercholestremia, hyperlipidemea, contributed to diabetes-related CVD risk more in women than in men.